The Role of T Cells in Ovarian Physiology and Infertility - Knapik, Laura O.; Paresh, Shubangi; Nabi, Dalileh; Brayboy, Lynae M. (Frontiers in Cell and Developmental Biology, 2022)
Infertility affects one in six couples worldwide, with more than 48 million couples affected internationally. The prevalence of infertility is increasing which is thought to be attributed to delayed child-bearing due to socioeconomic factors. Since women are more prone to autoimmune diseases, we sought to describe the correlation between ovarian-mediated infertility and autoimmunity, and more specifically, the role of T cells in infertility. T cells prevent autoimmune diseases and allow maternal immune tolerance of the semi-allogeneic fetus during pregnancy. However, the role of T cells in ovarian physiology has yet to be fully understood.